Nitrogen Retention in a Restored Tidal Stream (Kimages Creek, VA) Assessed by Mass Balance and Tracer Approaches. Issue 5 (1st September 2014) - Bukaveckas, Paul A.; Wood, Joseph
Abstract : Tidal streams are attractive candidates for restoration because of their capacity to retain nutrients from upland and estuarine sources. We quantified N retention in Kimages Creek, VA, following a dam breach that restored its historical (pre‐1920) connection to the James River Estuary. Estimates of N retention derived from mass balance analysis were compared to tracer‐based retention estimates obtained by injecting NH4 Cl during an incoming tide and measuring recovery on the outgoing tide. The injection experiments showed that dissolved inorganic N (DIN) retention in the restored tidal and nontidal segments was similar to nearby streams and previously published values. These data suggest that the stream has attained expected levels of functioning less than 2 yr after restoration despite 80 yr of impoundment. The mass balance analysis provided additional information for restoration assessment as this approach allowed us to track multiple N fractions. These results showed that DIN retention was offset by export of total organic N resulting in net loss of total N from the restored creek. Seasonal variation in DIN retention was significantly and positively related to tidal exchange volume and ecosystem metabolism (gross primary production and respiration). Our findings show that existing methods for measuring nutrient retention in nontidal streams can be adapted to the bidirectional flow patterns of tidal streams to assess restoration effectiveness.